The Role of the Gut-Liver Axis in Metabolic Dysfunction-Associated Fatty Liver Disease - Martín-Mateos, Rosa; Albillos, Agustín (Frontiers in Immunology, 2021)
The complex interplay between the gut microbiota, the intestinal barrier, the immune system and the liver is strongly influenced by environmental and genetic factors that can disrupt the homeostasis leading to disease. Among the modulable factors, diet has been identified as a key regulator of microbiota composition in patients with metabolic syndrome and related diseases, including the metabolic dysfunction-associated fatty liver disease (MAFLD). The altered microbiota disrupts the intestinal barrier at different levels inducing functional and structural changes at the mucus lining, the intercellular junctions on the epithelial layer, or at the recently characterized vascular barrier. Barrier disruption leads to an increased gut permeability to bacteria and derived products which challenge the immune system and promote inflammation. All these alterations contribute to the pathogenesis of MAFLD, and thus, therapeutic approaches targeting the gut-liver-axis are increasingly being explored. In addition, the specific changes induced in the intestinal flora may allow to characterized distinctive microbial signatures for non-invasive diagnosis, severity stratification and disease monitoring